Indicadores de gestión en las operaciones del servicio y la satisfacción del cliente en empresas de seguridad privadas medianas de la ciudad de Guayaquil - Abril Álvarez, Ángelo Alfredo (2022)
Management control is defined as the monitoring and evaluation of the execution of the activities of a company in order to ensure that the goals set are achieved. The general objective was to analyze the management indicators in service operations for customer satisfaction in medium-sized private security companies in the city of Guayaquil. The research methodology involved a mixed approach, descriptive type, inductive method, including a theoretical method, the techniques used were the survey and interview. The first was made up of a sample of 30 organizations through a questionnaire of 18 questions divided into five dimensions such as service expectations, time, resources, quality and user opinion, on the other hand, the second was given with seven questions about management. The results of the management indicators revealed that expectations in 36.7%, time in 46.7% and quality in 36.7% are the factors of greatest strength in the service operations of private security companies. On the other hand, the resources and the opinion of the user presented weaknesses in 40%, which mark a negative impact on the perception of the organizations to whom they provide their services. The proposal was subject to technology for better communication with the client, staff training and control of strategies together with descriptions of support resources, managers and a calendar of activities, as well as indicators such as the CSAT, rate of resolved complaints, participation of the client, among others. It is concluded that it is important to take into account the opinion of the administrators about some alternative, as well as the clients in order to develop better strategies.